Efektivitas Program Gumregah (Gerakan Terpadu Masyarakat Mengelola Sampah) Dalam Rangka Menekan Jumlah Sampah Organik Di Kecamatan Banyumanik - Satrio Gilang Faturrahman; wahid Abdulrahman (Journal of Politic and Government Studies, 2026)
The issue of urban waste in Indonesia particularly household organic waste continues to escalate alongside population growth, urbanization, and shifting consumption patterns. As a metropolitan city in Central Java, Semarang faces significant waste management challenges; consequently, the Semarang City Government initiated the Gumregah Program (Integrated Community Movement for Waste Management) as a community based effort to reduce waste. This study aims to analyze the effectiveness of the Gumregah Program in curbing the volume of organic waste in Banyumanik District. The research employs public policy effectiveness theory, utilizing the effectiveness indicators proposed by Duncan and Steers: goal attainment, integration, and adaptation. However, the program's effectiveness is hindered by limited facilities, inconsistent community participation, and uneven program support.